Quality impact of online database in selected universities in Malaysia - Abdullah, Adlina; Othman, Roslina; Mohd. Tamrin, Mohd. Izzuddin (2020)
Growing interests is going on among researchers to inquire the effectiveness of subscribed library online databases. However, a few studies on the impact of library online databases among scholars in Malaysia. The major objective of this research is to evaluate the effectiveness of library online databases. This study used a survey questionnaire to collect and the data was analyzed using SPSS (latest version). The results obtained showed that the subscription of library online database are still relevant in the academic environment